BIM and Collaborative Practices. Expertise and Skills from the Digital Environment - Maria Antonietta Esposito; Alessandra Donato; Filippo Bosi (Agathón)
The digital management of the construction process is required for sustainability. It imposes the definition of new roles and responsibilities and – consequently – makes it necessary to introduce new professional figures that are able to perform specific organizational and management tasks and functions in the scope of BIM process management. The contribution offers food for thought on the transversal and digital skills (soft skills) required by these professional figures on the basis of a critical analysis of examples reported in the literature, experiences and changes triggered by the adoption of the BIM methodology with respect to new activities, knowledge, skills, roles and responsibilities related to the professional figure.